Mechanisms and Application of Gas-Based Anticancer Therapies - Peng Ji; Kexin Yang; Qingqing Xu; Guilin Qin; Qianyu Zhu; Ying Qian; Wenshui Yao (MDPI AG, 2023)
Cancer is still one of the major factors threatening public health, with morbidity and mortality rates at the forefront of the world. Clinical drawbacks, such as high toxicity and side effects of drug therapy, and easy recurrence after surgery affect its therapeutic effect. Gas signaling molecules are essential in maintaining biological homeostasis and physiological functions as specific chemical substances for biological information transfer. In recent years, the physiological regulatory functions of gas molecules in the cancer process have been gradually revealed and have shown broad application prospects in tumor therapy. In this paper, standard gas therapies are classified and introduced. Taking H2, CO2, NO, CO, H2S, and SO2 gases as examples, the research progress and application of gas therapies in malignant tumors are mainly introduced in terms of biological characteristics, anticancer mechanisms, and treatment strategies. Finally, the problems and prospects for developing gases as anticancer drugs are outlined.